HIV incidence trends in Brazil and neighboring countries: an ecological and analytical study on public health - dos Anjos, Thiago Augusto Ferreira; Monteiro, Aline Moraes; Sardinha, Daniele Melo; Figueira, Luiza Raquel Tapajós; Silva, Marcos Jessé Abrahão; Marinho, Rebecca Lobato; Kimura, Mayara Annanda Oliveira Neves; Soares, Tamires de Nazaré; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Public Health, 2025)
IntroductionThe Human Immunodeficiency Virus (HIV) is a global public health problem. In Latin America this problem is aggravating and widespread, with regard to the countries bordering Brazil, the notification of cases among men and women shows an aggravating panorama, which requires actions and services aimed at monitoring and changing this chain of transmission.ObjectiveTo investigate the trend of HIV incidence in Brazil and neighboring countries from 2013 to 2023.MethodsAn ecological, retrospective and quantitative study on HIV in Brazil and border countries, Excel 2019 and R language were used to process and analyze the data, it is worth noting that no data was found for French Guiana.Results and discussionBased on the analyses performed, including violin statistics, linear regressions, ARIMA models, and comparability tests, it was possible to identify relevant patterns among the countries observed. Bolivia showed consistent and statistically significant growth in the HIV incidence rate, with an increase of 83.8% over the decade analyzed (R2 = 0.67; p = 0.0022). On the other hand, Guyana, although still among the countries with the highest incidence rates, showed a significant reduction of 31.6%. Suriname remained one of the countries with the highest rates throughout the period, exceeding 100 cases per 100,000 inhabitants in certain years. Spatial analysis revealed considerable disparities, particularly in border areas, where there is a higher concentration of cases, indicating the need for targeted public policies and shared surveillance efforts. Countries such as Peru, Colombia, and Paraguay also showed a growing trend, while Argentina, Uruguay, and Venezuela showed a decline or stagnation, although in some cases this apparent stability may be linked to underreporting.ConclusionSome countries need to strengthen actions and services to monitor and break the chain of transmission, and implement public policies, as well as re-evaluate and ensure in countries with socio-economic and political crisis, in order to transform this aggravating panorama in Latin and South America.